Autoimmune pancreatitis mimicking Klatskin tumour on radiology. (9th April 2015) - Hadi, Yousaf Bashir; Sohail, Abdul Malik Amir Humza; Haider, Zishan
Abstract : Autoimmune pancreatitis (AIP) is categorised into two distinct types, AIP type 1 and 2. Although there can be multisystem involvement, rarely, the cholangitis associated with AIP can present radiologically in a manner similar to that of Klatskin tumour. We present the case of a 65-year-old man who was almost misdiagnosed with a Klatskin tumour because of the similarity in radiological features of the two aforementioned clinical entities. The patient presented with a history of jaundice, pruritus and abdominal pain, and work up showed deranged liver function tests, elevated cancer antigen 19-9 levels and positive antinuclear antibodies. CT scan of the abdomen showed findings suggestive of Klatskin tumour but due to diffuse enlargement of the pancreas and surrounding low-attenuation halo found on a closer review, a diagnosis of AIP was performed. The patient was started on standard corticosteroid therapy and responded well, with complete resolution of the radiological findings.